Spatial immune heterogeneity in a mouse tumor model after immunotherapy - Smahel, Michal; Johari, Shweta Dilip; Smahelova, Jana; Pfeiferova, Lucie; Nunvar, Jaroslav (Cancer science, 2025)
Cancer immunotherapy is increasingly used in clinical practice, but its success rate is reduced by tumor escape from the immune system. This may be due to the genetic instability of tumor cells, which allows them to adapt to the immune response and leads to intratumoral immune heterogeneity. The study investigated spatial immune heterogeneity in the tumor microenvironment and its possible drivers in a mouse model of tumors induced by human papillomaviruses (HPV) following immunotherapy. Gene expression was determined by RNA sequencing and mutations by whole exome sequencing. A comparison of different tumor areas revealed heterogeneity in immune cell infiltration, gene expression, and mutation composition. While the mean numbers of mutations with every impact on gene expression or protein function were comparable in treated and control tumors, mutations with high or moderate impact were increased after immunotherapy. The genes mutated in treated tumors were significantly enriched in genes associated with ECM metabolism, degradation, and interactions, HPV infection and carcinogenesis, and immune processes such as antigen processing and presentation, Toll-like receptor signaling, and cytokine production. Gene expression analysis of DNA damage and repair factors revealed that immunotherapy upregulated Apobec1 and Apobec3 genes and downregulated genes related to homologous recombination and translesion synthesis. In conclusion, this study describes the intratumoral immune heterogeneity, that could lead to tumor immune escape, and suggests the potential mechanisms involved.
Keywords: tumor microenvironment; regulace genové exprese u nádorů; Humans; DNA repair; cancer immunotherapy; únik nádoru z imunitní kontroly; Female; mutace; lidé; Immunotherapy; zvířata; sekvenování exomu; myši; Mice; Papillomavirus Infections; ženské pohlaví; mutation; Neoplasms; Tumor Microenvironment; Tumor Escape; infekce papilomavirem; nádorové mikroprostředí; nádory; intratumoral heterogeneity; Animals; Mutation; Gene Expression Regulation, Neoplastic; imunoterapie; Disease Models, Animal; Exome Sequencing; modely nemocí na zvířatech